Pemberdayaan Petani dalam Identifikasi dan Pengendalian Gulma dengan Teknologi Hayati di Lahan Pertanian Kelurahan Kulaba (Maco'ou : Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to enhance the capacity of farmers in Kulaba Village to identify and manage weeds in an environmentally friendly manner using biological technology. The main problems faced by the partners include limited knowledge of weed species and reliance on chemical herbicides. The activities were conducted through a participatory approach, including weed identification training, education on biological control, hands-on bioherbicide formulation using local materials, and field application. The results indicated significant improvements in four key areas: weed identification, understanding of biocontrol principles, formulation skills, and willingness to implement in the field. Most participants showed high enthusiasm and began applying the techniques in their own fields. The program outputs include a practical guidebook, a simple bioherbicide formula, and enhanced partner capacity in sustainable weed management. Program success was supported by active farmer participation, availability of local resources, and practice-based education. This initiative is expected to serve as a replicable model for other agricultural areas facing similar issues.